Sufi women of South Asia: veiled friends of God - Aftab, Tahera (Woman and gender, 2022)
Introduction -- Part I. Sufis, Sufism, and Transformations: 1. Setting the Scene -- 2. The Sufi Texts: From Imagination to the Inscribed Word -- 3. The Sufi Gaze: Perception of Women by Male Sufis -- 4. The Sufi Gaze: Sufi Perception of Family -- 5. The Sufi Gaze: Interaction with Maidservants and Women of Ill Repute -- 6. Women's Presence in Sufi Silsilas -- 7. Sufi Lodges: Fencing the Sacred and the Profane -- 8. Sufi Shrines: Manifesting the Deceased Sufi -- Part II. Biographies of Sufi Women: 9. Biographical Notices of Sufi Women by Time Period -- 10. Biographical Notices of Sufi Women according to Their Specific Status -- 11. Biographical Notices of Women Sufis Based on Oral Traditions Collected by Visiting Their Shrines -- 12. Sufi Women Identified by Name Only -- Conclusions -- Glossary -- Bibliography -- Index.